Tai Chi for balance and postural control in people with peripheral neuropathy: A scoping review - Mingxiao Yang; Carrie Shao; Cassie Shao; Kirin Saint; Peter M. Wayne; Ting Bao (Complementary Therapies in Medicine, 2024)
Background: Peripheral neuropathy can affect balance and increase fall risk. Tai Chi is known to activate neuromuscular systems and may help improve balance and postural control. We conducted a scoping review of clinical studies that evaluated the impact of Tai Chi on balance and related neurobiological outcomes among individuals with peripheral neuropathy. Methods: We systematically searched three databases from inception to December 19, 2023 and identified 11 eligible clinical studies. We extracted trial information from each study and performed a qualitative study features analysis to summarize the clinical evidence and neurobiological mechanisms of Tai Chi in regulating balance among people with peripheral neuropathy. Results: We found that among 508 participants with clinical peripheral neuropathy, Tai Chi significantly improved single leg stance, 6-min walk, timed up-and-go tests, and gait speed when measured pre- and post-exercise. However, the differences between Tai Chi and sham exercise control that involved active calisthenics and stretching exercises were not statistically significant. Studies that used quantitative sensory testing showed that Tai Chi was associated with significant increases in plantar vibration and tactile sensitivity. The effect of Tai Chi on postural control varied depending on plantar sensory loss status, and results on muscle strength remained mixed. Other neurobiological effects involve strengthening muscle performance and proprioception and consolidating cognitive awareness of walking strategy and practical behavioral techniques. Conclusions: The findings indicated that Tai Chi may enhance balance, postural control, and gait speed in patients with peripheral neuropathy, possibly through sensory restoration, although further research is needed to confirm this. Whether Tai Chi improves muscle strength or other gait health parameters is inconclusive. Rigorous randomized clinical trials should be conducted to determine the effect of Tai Chi on balance in this population by measuring functional balance and quantitative sensory outcomes.